Prospects for widespread adoption of organic-based fertilizers in the Philippines: A rapid appraisal - Roehlano M. Briones; Helena Luz C. Pastolero; Ivory Myka R. Galang (Philippine Institute for Development Studies (PIDS), 2024)
Modern conventional agriculture has relied heavily on inorganic fertilizers to achieve higher crop yields. However, concerns have arisen regarding its ecological and economic sustainability, given its impact on soil health on-site, on pollutants off-site, and of recent bouts of soaring fertilizer prices. This paper reports on a rapid appraisal of the current state and potential expansion of organic fertilizer utilization and availability in the Philippines. The study finds that combining inorganic and organic-based fertilizers allows for a balanced realization of the advantages of each type. Policies and programs of the government do promote both organic agriculture and balanced fertilization, although the budget is strongly biased towards incentivizing farmer purchases of inorganic fertilizer. Policy implications of the study are: 1) Strengthen the NOAP by a) expanding the implementation of PGS and b) aggressively rolling out organic labeling of packaged organic produce; 2) Review the regulatory system and competition oversight for organic fertilizers and biofertilizers; 3) Adopt a phased repurposing of fertilizer subsidy by gradually shifting the allocation from inorganic fertilizer to organic fertilizers, biofertilizers, and area-based R&D to promote adaptive BFS, including soil mapping of all agricultural land in the country; 4) Beyond R&D, DA must invest heavily in extension to promote the widespread adoption of adaptive BFS; 5) Implement a value chain program for the development of the biofertilizer and organic fertilizer industry; 6) Anchor the value chain program on support for commercial networks of private corporations and capacitated FOs, and coordinated with the distribution of organic fertilizer and biofertilizer vouchers; and 7) Integrate value chain development of organic fertilizers and biofertilizers with development of the livestock, poultry, and agro-processing industry.
Keywords: 330; sustainable agriculture; circular agriculture; biofertilizer; organic fertilizer; organic agriculture; integrated nutrient management